Azobenzene crystal polymorphism enables tunable photoinduced deformations, mechanical behaviors and photoluminescence properties. Issue 26 (17th June 2021) - Hao, Yunhui; Gao, Lei; Zhang, Xiunan; Wei, Rongli; Wang, Ting; Wang, Na; Huang, Xin; Yu, Haifeng; Hao, Hongxun
Abstract : Tuning polymorphism in azobenzene molecular crystals enables them to exhibit a remarkable difference in photomechanical deformations, mechanical behaviors and luminescence properties. Abstract : Stimuli-responsive molecular crystals are fascinating for their potential as adaptive smart materials. However, achieving crystals that could respond to multiple stimuli and perform multiple functionalities simultaneously is still a challenging task. Herein, we report the fabrication and preparation of polymorphic crystals with multiple stimuli of a photoactive azobenzene derivative, trans -4-cyano-4′-oxethyl azobenzene (AzC2 ). Different polymorphic forms of AzC2 exhibit remarkable different photoinduced deformations, mechanical behaviors and photoluminescence properties. Upon UV irradiation, although both polymorphic forms undergo reversible photomechanical bending motions, Form I bent away from the light source while Form II bent towards the light source. Upon exertion of external mechanical stress, Form I tended to break whereas Form II exhibited elastic deformation. Furthermore, being excited at 325 nm, the block crystal of Form I exhibited a relatively strong green-yellow emission while a very weak red fluorescence emission was observed from the thicker Form II crystal. These different properties can be attributed to different molecular packings rather than molecular conformations. The present work provides an effective strategy to construct multiple stimuli-responsive crystal materials with potential applications in actuators, switches and sensors.